Portrait of a Contender: Ismael Arinas Pellón - Pellón, Ismael Arinas (Language at Work - Bridging Theory and Practice, 2010)
“Language at Work – Bridging Theory and Practice” recently connected with Ismael Arinas Pellón, a foreign language lecturer at the Universidad Politécnica de Madrid, Spain. Ismael had interesting insight to share with “Language at Work” readers about the role of foreign language usage from a personal and professional perspective.